Sabun Mandi Natural Herbal Hasil Adaptasi dari Naskah Pengobatan Tradisional - Hanani, Tifa (Masyarakat Pernaskahan Nusantara, 2023)
Text editions of traditional medicinal texts resulting from research by philologists have not been widely used as an alternative to body care products, particularly natural bath soap. Two of them are manuscripts of traditional medicine from the collection of the National Library of Indonesia entitled Usada (KBG 357) and Tetamba Jampi (BR 55). The purpose of this research is to present an eco-friendly natural bath soap with herbal ingredientsadapted from ancient manuscripts. In this regard, this research focuses on benefits and decomposition of traditional spices in manuscripts that can be used as ingredients for making natural bath soap. The results of this study can be seen that the herbs contained in traditional medicine texts can be used as an alternative herbal ingredients for making eco-friendly natural bath soap because of their benefits for the skin. In addition to having cultural and profit values, namely as an alternative to creative industry products based on local wisdom, making eco-friendly soap also has cultural values, namely preserving the contents of ancient manuscripts. === Edisi teks naskah pengobatan tradisional hasil riset para pakar filologi belum banyak dimanfaatkan sebagai alternatif produk perawatan tubuh, khususnya sabun mandi natural. Dua diantaranya yaitu naskah pengobatan tradisional koleksi Perpustakaan Nasional Republik Indonesia berjudul Usada (KBG 357) dan Tetamba Jampi (BR 55). Tujuan dari penelitian ini adalah menghadirkan sabun natural ramah lingkungan dengan bahan herbal yang diadaptasi dari naskah kuno. Berkenaan dengan itu, penelitian ini berfokus pada penguraian rempah tradisional dalam naskah yang dapat digunakan sebagai bahan pembuatan sabun mandi natural beserta manfaatnya. Hasil dari penelitian ini dapat diketahui bahwa herbal yang terkandung dalam teks naskah pengobatan tradisional dapat digunakan sebagai alternatif bahan herbal pembuatan sabun mandi natural ramah lingkungan karena manfaatnya bagi kulit. Selain bernilai budaya dan profit yaitu sebagai alternatif produk industri kreatif berbasis kearifan lokal, pembuatan sabun mandi ramah lingkungan juga bernilai budaya yaitu melestarikan kandungan naskah kuno.